TO DETERMINE THE PATHOGENIC PROFILE AND ANTIMICROBIAL SUSCEPTIBILITY PATTERN IN BRONCHIECTASIS PATIENTS IN SOUTHERN KPK - Qaisar Iqbal; Tahir Ullah Khan; Nafid Ullah Khan; Mohib Ullah Khan; Wajid Khan; Kamran Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Objective: To determine the pathogenic profile and antimicrobial susceptibility pattern in bronchiectasis in southern KPK. Materials and Methods: This Cross-sectional, descriptive study was conducted in department of Medicine, MTI - DHQ Hospital, Bannu from 1st December, 2024 to 31st May, 2025. Patients included in this study were known to have bronchiectasis on the basis of radiological findings and presenting to pulmonology OPD with fever and copious amount of sputum for more than two weeks. Sputum cultures were collected according to standard laboratory protocol and analyzed as per established guidelines. Data was analyzed through latest SPSS Version. Results: In this study, a total of 76 patients with bronchiectasis were assessed with sputum culture and antibiotic susceptibility pattern of the common respiratory pathogens were measured. Every respiratory pathogen was assessed for 5 common antibiotics and antibiotic susceptibility pattern was established.Conclusion: Knowledge of the pathogenic profile and antibiotic susceptibility pattern of common respiratory pathogens in bronchiectasis is important in terms of developing effective treatment strategies. Further research to effectively address the issue of antibiotic resistance and develop novel antibiotics id is needed.